A case study of scientific literacy in natural science subject using rasch analysis model (RAM). Issue 1 (March 2021) - Mubarokah, N; Permanasari, A; Eliyawati, E
Abstract: The study aims to analyze junior high school students' scientific literacy in Natural Science subjects. The study used a case study method. There were 70 students of IX grade in a private junior high school in West Bandung Regency. Respondents consisted of 40 boys and 30 girls with an average age of 15 years old. The instrument used was a written test consisting of 30 simple multiple-choice questions for three aspects of scientific literacy, which were scientific knowledge, scientific competencies, and attitudes toward science. The data analysis used Rasch Analysis Model (RAM) and assisted by Winsteps 4.4.5. The results being discussed are the person and item reliability, variable maps, and differential item functioning (DIF). The results show that the average scientific literacy ability of students falls into the low category, and some questions have gender biases. Thus, scientific literacy needs to be promoted and involved effectively in teaching-learning activities to get students used to the scientific literacy environment in their learning programs during school years.